Effectivity and Safety of Endo-1,4 -xylanase (Xylanase), Endo-1,3(4) beta-glucanase (Beta-glucanase), Endo-1,4 beta-glucanase (Cellulase), and α Amylase as A Growth Promoter in Broiler Chickens - Aurellia, Sharon; Fadholly, Amaq (IPB University, 2025)
This study evaluates the effectivity and safety of Endo-1,4 -xylanase (Xylanase), Endo-1,3(4) beta-glucanase (Beta-glucanase), Endo-1,4 beta-glucanase (Cellulase), and α Amylase that packed in Ronozyme-AX ct (MGHSPHYT+) as an alternative to antibiotic growth promoter. A total of 64 chickens were used, divided into four groups, with each group divided into two replicates, 8 chickens per replicate. The groups were divided into treatment group, and groups administered with the different dosage of supplementation, namely 184, 230, and 276 gram/ton feed for 28 days, consecutively. Parameters such as weekly weight gain, final weight, feed conversion ratio (FCR), and carcass weight were observed to determine growth performance. Meanwhile, parameters such as mortality, blood hematology and biochemistry were observed to determine the safety of the supplementation. Based on the results, there was a significant difference on weekly weight gain, particularly in the second week, and in the final weight, with the group administered with 184 gram/ton feed showing the highest result. Meanwhile, other parameters such as FCR and carcass weight did not show any significant difference. This may be due to the enzymes not working directly to increase feed utilization but work with improving nutrient digestibility and utilization in the body. The safety parameters showed that the supplementation was relatively safe as no significant difference was observed in mortality, blood constituents and biochemistry.